Mechanical property and fracture characteristics of carbon fiber reinforced aluminum matrix composites prepared by friction stir welding - Y.J. Lu; Q.L. Liu; Y.D. Liu; C. Yu; H.X. Chen; Y.X. Chen; Y.J. Liu (Journal of Materials Research and Technology)
In this study, the mechanical performance and fracture characteristics of carbon fiber (Cf) reinforced aluminum composites (CF@Al) manufactured through friction stir welding was investigated by in-situ tensile test coupling scanning electron microscopy, electron backscatter diffraction and digital image correlation, and the fracture behavior and microstructural evolution under tensile loading was elucidated. The results show a 16 % improvement in tensile strength and a significant work hardening effect in the CF@Al composites compared to pure aluminum, while maintaining good ductility. The carbon fibers were found to be the primary load-bearing sites, with fracture mechanisms involving fiber breakage and fiber pull-out. The outcomes enhance our understanding of the structural behavior of CF@Al composites under tensile stress.